Apparent 'electrocatalytic' activity of multiwalled carbon nanotubes in the detection of the anaesthetic halothane: occluded copper nanoparticles. - Dai, X; Wildgoose, G; Compton, R (2006)
The electrocatalytic detection of the anaesthetic halothane on a multiwalled carbon nanotube modified glassy carbon electrode is reported with a low limit of detection of 4.6 microM. A thorough investigation of the underlying cause of this apparent catalytic effect is undertaken by comparing the response of various carbon electrodes including glassy carbon, basal- and edge-plane pyrolytic graphite electrodes (bppg and eppg respectively) to increasing additions of halothane. The reduction of halothane is shifted by 250-300 mV to more negative potentials at an eppg electrode than that observed at the GC-CNT electrode. Therefore the results of this investigation show that, surprisingly, the electrocatalysis is not solely due to the introduction of edge-plane-like defect sites on the carbon nanotubes as is commonly found for many other substrates showing favourable voltammetry at nanotube modified electrodes. Instead, we reveal that in this unusual case the electroactive sites for the reduction of halothane are due to the presence of copper nanoparticles occluded within the carbon nanotubes during their production, which are never completely removed by standard purification techniques such as acid washing. This is only the third known case where apparent electrocatalysis by carbon nanotube modified electrodes is due to occluded metal-related nanoparticles within the nanotube structure, rather than the active sites being the edge-plane-like defect sites on the nanotubes. Furthermore this is the first case where the active sites are nanoparticles of copper metal, rather than metal oxide nanoparticles (namely oxides of iron(II)/(III)) as was found to be the case in the previous examples.